1992
DOI: 10.1002/anie.199204371
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Structure and Reactivity of a Stannaketenimine

Abstract: 9] Crystal structure analysis of 1: H,SO,, M, =114.08, a = 628.5(3), b = 1420.0(4), c =773.4(3) pm, 2 = 8, V, = 0.6902 nm', space group Pbca, crystal size 0.69 x 0.66 x 0.21 mm', four-circle diffractometer, Mo,. radiation, 912 measured reflections, 713 independent reflections with J > 0, numerical absorption correction, 64 refined parameters, R = 0.047, R, = 0.041. Further details of the crystal structure investigation may be obtained from the Fachinformationszentrum Karlsruhe, Gesellschaft fur wissenschaftlic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 31 publications
(2 reference statements)
3
62
0
Order By: Relevance
“…These properties of 5 c ± e resemble those of the reported stannaketenimine, [18] and indicate sharp contrasts to those of 1-phospha-3-silaallene [19] and 1-phospha-3-germaallene, [20] which reportedly have cumulative-compound character.…”
Section: Resultsmentioning
confidence: 45%
See 2 more Smart Citations
“…These properties of 5 c ± e resemble those of the reported stannaketenimine, [18] and indicate sharp contrasts to those of 1-phospha-3-silaallene [19] and 1-phospha-3-germaallene, [20] which reportedly have cumulative-compound character.…”
Section: Resultsmentioning
confidence: 45%
“…As for the tin analogues of silaketenimines, a stannnaketenimine, [{2,4,6-(CF 3 ) 3 C 6 H 2 } 2 -SnCNMes], has been isolated as a stable compound, and its X-ray structural analysis revealed that it has a bent SnCN structure bearing a pyramidally coordinated tin atom. [18] It has been proposed that the Sn À C bond in the SnCN structure, which was found to be longer than an Sn À C single bond, may be described as a double p-donor ± acceptor interaction. Recently, Escudie ¬ et al have reported the spectroscopic observation of two new species having an > MCE-(M Group 14 element; E Group 15 element) structure, for example, 1-phospha-3-silaallene [Tip(Ph)SiCPMes*] (Tip 2,4,6-(iPr) 3 C 6 H 2 ; Mes* 2,4,6-(tBu) 3 C 6 H 2 ) [19] and 1-phospha-3-germaallene [Mes 2 Ge C PMes*].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last case to be considered is the stannylene-isocyanide adduct 1 that is to some extent an extreme system as its linear geometry suggests little or no -type interactions. 4 In agreement with this assumption, geometry optimization and subsequent frequency calculation gave ν(CN) = 61 cm 1 . This value is in fact slightly greater than what was observed for any of the systems in the set of model compounds.…”
Section: Bonding and Back-bonding Interactions Determined By Constraimentioning
confidence: 62%
“…9 In general, metal-mediated coupling and polymerization of unsaturated organic molecules are important industrial processes, 10 and the synthesis of heterocycles resulting from coupling and cycloaddition reactions of isocyanides with other heteroelement unsaturated species is a widely used technique. 11 [4] During our investigations of the chemistry of the adduct 5, it was realized that its ν(CN) stretching band is shifted to slightly lower wave number relative to the analogous stretching frequency of the free isocyanide. 7a This prompted us to investigate the possibility of Ge-C -bonding in 5 i.e.…”
Section: Introductionmentioning
confidence: 99%